Role of Artificial Intelligence (AI) in Globalizing World - Aryal, Rounik Raj (KDCBAR Law Journal, 2025)
The wide increment and integration of Artificial Intelligence (AI) into global pathway has transformed the dynamics of globalization that has offered unparalleled momentum and increased the challenges. This articles explores the multidimensional role of AI in a rapidly globalizing world, highlighting its historical development, technological transformation and significant influence on economic, social and political scenarios. This paper emphasizes how human cognitive has developed over the historical timeframe, especially with Artificial Neural Networks, replicating human logic to execute the challenging tasks. With the advent of AI from initial symbolic reasoning to present machine learning and neural networks, AI has profoundly affected the industries, jobs and overall global relations. AI has restructured the business models, improving the decision-making, boosting efficiency, which has sometimes provoked fears of automation related job displacement, data privacy issues, digital gaps and geopolitical power imbalances. Economically prosperous countries such as U.S. and China are at the frontline of AI adoption and fostering the disproportionate gains, while emerging economies are facing obstacles including limited infrastructure, skills shortages and limited access of technology. However, AI has offered the tools to resolve social dilemmas and achieve inclusive growth. This article highlights the international collaboration, ethical regulation and sustainable policy structures as it is necessary to mitigate the AI gap. Conclusively, AI is an enhancer of global change, meantime, researches urges responsible innovation to ensure its benefits are equitably shared, fostering more inclusiveness, interconnectedness and sustainable growth in the future.